Tax Overbooking Of Msme Individuals On The Impact Of The Harmonization Of Tax Regulation Socialization - Dedy Triyono; Adhityawati Kusumawardhani (International Journal of Organizational Behavior and Policy, 2022)
The COVID-19 pandemic situation made the Government enact Law No. 7 of 2021 about Harmonization of Tax Regulations (Law 7/2021) which aimed to improve the budget and increase taxes. The purpose of this study was to identify the tax overbooking practices of Micro, Small and Medium Enterprises (MSME) owned by individuals in light of the Law 7/2021 socialization. The methodology used is qualitative. Respondents are East Java-based individuals who own MSMEs. The imposition of income tax rates in Law 7/2021 is that individual taxpayers and individual taxpayers who owned MSMEs whose income is approximately Rp. 500 million a year, are exempt from paying final income tax of 0.5% in accordance with the rates in government regulation No. 23 of 2018. In reality, individual taxpayers who owned MSMEs and had already paid taxes in accordance with the rates specified in government regulation no. 23 of 2018 in January and February 2022 may make a tax overbook of the tax already paid if the annual turnover exceeds Rp 500 million in the month in which the calculated turnover exceeds Rp 500 million. This is because the Directorate General of Taxes' socialization efforts during the Covid 19 pandemic received little attention from taxpayers who owned MSMEs.